Software Vulnerability Databases - Kekül, Hakan; Ergen, Burhan; Arslan, Halil (Osman SAĞDIÇ, 2021)
Predicting the vulnerability propensity of a software component is one of the challenging research areas of software engineering. Having prior knowledge of a component's vulnerability propensity can significantly reduce testing effort and time. Identifying and classifying software vulnerabilities will assist developers in making the right decision in software development. For this reason, vulnerabilities detected in software have been recorded in databases for a very long time. Many databases have been created by different research groups. This diversity has provided advantages and disadvantages to each database. In this study, a systematic list of the most up-to-date and accessible ones used in the literature was created to help researchers decide which database to use in their studies. There is a review and comparison of many different databases used in software vulnerability detection and classification. At the end of the study, the results are presented and guiding recommendations for future work are given.

Bir yazılım bileşeninin güvenlik açığı eğiliminin öngörülmesi, yazılım mühendisliğinin zorlayıcı araştırma alanlarından biridir. Bir bileşenin güvenlik açığı eğilimi hakkında önceden bilgi sahibi olmak, test çabasını ve süreyi önemli ölçüde azaltabilir. Yazılım güvenlik açıklarının belirlenmesi ve sınıflandırılması geliştiricilere yazılımın geliştirilmesinde doğru karar verme noktasında yardımcı olacaktır. Bu sebeple yazılımlarda tespit edilen açıklar çok uzun zamandır veri tabanlarına kaydedilmektedir. Farklı araştırma grupları tarafından pek çok veri tabanı oluşmuştur. Bu çeşitlilik her veri tabanına kendi içinde avantajlar ve dezavantajlar sağlamıştır. Bu çalışmada araştırmacıların çalışmalarında hangi veri tabanını kullanacaklarına karar vermelerine yardımcı olmak ve literatürde kullanılan en güncel ve erişime açık olanların sistematik bir listesi oluşturulmuştur. Yazılım güvenlik açığı tespiti ve sınıflandırmasında kullanan birçok farklı veri tabanının incelenmesi ve karşılaştırması yer almaktadır. Çalışmanın sonunda sonuçlar sunulmuş ve gelecekteki çalışmalar için yönlendirici tavsiyeler verilmiştir.
Yazılım Güvenlik Açığı Veri Tabanları
Keywords: Engineering; Mühendislik